EVALUATION OF POLYMORPHONUCLEAR IMMUNE CELLS IN BIOCOMPATIBILITY TEST DFLP SPONGE CARTILAGE SCAFFOLD, ADIPOSE-DERIVED MSC AND SECRETOME WITH CARTILAGE INJECTION MODEL - Brilliant Citra Wirashada; Dwikora Novemberi Utomo; Lukas Widhiyanto (Journal Orthopaedi and Traumatology Surabaya, 2020)
Background: In recent years, Freeze-Dried Scaffold Bovine Cartilage has been widely used as an alternative therapy for joint cartilage defects. This study aims to determine the biocompatibility of scaffold without involving implantation which provides clinical reports as expected through the evaluation of post-implantation chondrocytes regeneration, biocompatibility markers of the scaffold, and biocompatibility of sponge cartilage scaffold involving cartilage defects New Zealand White Rabbit. Methods: This experimental in-vivo study was conducted for four weeks. Rabbits were divided into 4 treatment groups: microfracture defect group with DFLP sponge cartilage scaffold (P1) implantation; Microfracture defect group with DFLP sponge cartilage scaffold-secretome implantation (P2); Microfracture defect group with DFLP sponge cartilage scaffold-adipose derived Mesenchymal Stem Cells (ADMSCs) (P3); Microfracture defect group without implantation (control). The evaluations of basophil, eosinophil, neutrophil, and polymorphonuclear (PMN) cells were done in the first 24 hours, 3 days, and 1 week after the treatment. The collected data will be analyzed statistically. Results: Research observations performed three times in the first, third, and seventh days. The results showed a small number of average Neutrophil (Neutrophil granulated) and PMN (segmented Neutrophils) cells both in the P2 and P3 groups compared with the control and the P1 group. Conclusion: In general, biocompatibility is not included on the cytotoxic effects including inflammatory reactions and post-cartilage scaffold sponge implantation (DFLP) with or without the addition of ADMSC and secretome in the white rabbit New Zealand cartilage defect associated with differences seen in eosinophils, basophils, neutrophils, also total PMN cells in four groups.